European Single Market and technical barriers to Latin American exports (SELA CaracasVE, 1993)
Identifies and analyses how the European Community has set about removing technical barriers to trade among its members. Examines the implications of this process for third countries and arrives at some conclusions. Makes proposals for further detailed work which would be of direct value to Latin American governments and exporters.
Bibliography: p.10-11